'THE MIND IS ITS OWN PLACE': AMELIORATION OF CLAUSTROPHOBIA IN A PATIENT WITH SEMANTIC DEMENTIA. Issue 11 (9th October 2013) - Clarke, Camilla; Fletcher, P; Cifelli, A; Warren, JD
Abstract : Specific phobia is defined as marked, persistent and excessive or unreasonable fear when in the presence of, or when anticipating an encounter with, a specific object or situation. 1 Here we describe amelioration of one common and disabling example, claustrophobia, following the onset of semantic dementia. Our patient had a clinical diagnosis of claustrophobia dating from her 20s and severe enough to cause her difficulties in daily life. She had habitually avoided lifts, windowless rooms, train travel and flying on account of her intense fear of being enclosed. At the age of 61, she developed a typical syndrome of semantic dementia led by progressive loss of facial recognition, anomic aphasia with loss of verbal and nonverbal knowledge and characteristic asymmetric (predominantly right sided) anterior temporal lobe atrophy on brain MRI. Around 7 years after onset of first symptoms her family reported that her previously severe claustrophobia had essentially disappeared: she would now enter small rooms without evident distress and happily participated in a longitudinal research study involving regular MRI scans. Specific phobias are thought to be mediated neuroanatomically via limbic and paralimbic circuitry, including the amygdala, anterior cingulate and insula. 2 These regions are all targeted in semantic dementia, while altered fronto–limbic connectivity has been described in frontotemporal lobar degeneration. 3 Our patient's newfound fearlessness may reflect an interaction of damaged limbic and autonomic responsivity with loss of the cognitive meaning of previously threatening situations. More broadly, her case illustrates how the brain constructs a private model of the world and invests this with emotional significance, and how this process can be modulated by pathological mental states: as recognised long ago by John Milton, and others.